Living on the edge of America : at home on the Texas-Mexico border - Maril, Robert Lee (Wardlaw book., 1992)
On the southern edge of America a diverse group of people lead ordinary lives in rather extraordinary circumstances. Mexican Americans, Anglos, and Mexican nationals meet there, in the subtropical beauty of the Rio Grande Valley and amid conditions of extreme poverty and social inequality, and create a distinctive blend of cultures, languages, and attitudes toward life. The stories that emerge are stories of individual victories, daily standoffs, and brutalizing defeats.